School Strategy to Prevent Bullying Through the Habit of Congregational Prayer in Muhammadiyah Elementary Schools - Supriyadi; Nadia Prasetya Retno Putri; Farah Abida Ryzqiyah; Reysniah Uswatun Hasanah; Salsabilla Octavia Putri (P3I UMSurabaya, 2024)
This study explores the role of congregational prayer in preventing bullying in schools. Using a qualitative phenomenological approach, data were collected through interviews, observations, and documentation, then analyzed with the Miles and Huberman interactive method. The results show that congregational prayer helps build character and internalize Islamic values, which serve as a strategy to prevent bullying. Key findings highlight several strategies: (1) fostering a positive and tolerant environment, (2) instilling Islamic character values, (3) intensive supervision, (4) student involvement, (5) enhancing self-awareness and empathy, (6) applying positive approaches to negative behavior, (7) providing real-life examples, (8) reinforcing anti-bullying commitments, (9) encouraging student role models, and (10) integrating Islamic values into daily school life. These efforts collectively create a supportive environment that reduces bullying incidents and promotes positive student behavior.